Comparative analysis of performance indicators determining winning and losing conditions of Selangor Red Giants in the MSC Final - Baharudin, Muhammad Afiq; Junaidi, Muhammad Fikri Iman; Mohamed, Muhamad Noor; Saiful Annur, Muhamad Safiq; Adnan, Mohd Aizzat; Mazaulan, Mardiana; Md Radzi, Noor Azila Azreen (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study utilizes video-based notational analysis to investigate key performance indicators influencing match outcomes for the Selangor Red Giants (SRG) during the MSC Final. By examining seven matches under both winning and losing conditions, the research evaluates critical variables such as objective control (Lord and Turtle), zoning tactics, and engagement dynamics ranging from ganks to full team fights. The findings aim to bridge the gap in esports performance literature, providing a data-driven framework for strategic planning and competitive optimization in professional gaming.